Additive for mixing raw materials of carbon-based ceramic friction material and preparation method of additive

By compounding the multi -wall carbon nanoprotor tubes of boron -nitride and modified polyether etherone, the problem of the problem of the brittleness and resistance of carbon -based ceramic friction materials in high temperature, high speed and heavy load conditions, and realized The mechanical performance of materials is improved and the service life is prolonged.

CN119350045AInactive Publication Date: 2025-01-24JIANGSU XINGUAN BRAKE TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411418059.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Carbon-based ceramic friction materials have high brittleness and weak impact resistance under high temperature, high speed and heavy load conditions, and are prone to thermal stress when connected to metal parts, resulting in early failure of the material.

Method used

Boron nitride-loaded multi-walled carbon nanotubes are used as functional fillers, compounded with modified polyether ether ketone, antioxidants and other additives. The mechanical properties and compatibility of polyether ether ketone are improved through chemical modification to form a dense composite structure.

Benefits of technology

It significantly enhances the mechanical performance and impact performance of composite materials, improves the carrying capacity and abrasion resistance of friction materials, maintains the stability of the material in high temperature environments, extends the service life of the material, and improves its processing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of additive processing, and particularly discloses an additive for mixing raw materials of a carbon-based ceramic friction material and a preparation method of the additive. The preparation method comprises the following steps: mixing a treated multi-walled carbon nanotube with a sodium borate and ethylenediamine aqueous solution, calcining at high temperature to obtain a boron nitride-loaded multi-walled carbon nanotube, and combining with a cross-linking agent to prepare a functional filler; adding ethylenediamine, 3, 3-diphenylpropylamine and palladium acetate into the prepared N-methyl pyrrolidone and polyether-ether-ketone solution to obtain modified polyether-ether-ketone; and mixing the modified polyether-ether-ketone, a functional filler, an antioxidant, a lubricant and N, N-dimethylformamide to obtain the additive for mixing the raw materials of the carbon-based ceramic friction material. The additive provided by the invention has good compatibility, can significantly improve the processing molding performance and mechanical strength of the friction material, and effectively reduces the wear rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of additives, and more specifically to an additive for mixing raw materials of carbon-based ceramic friction materials and a preparation method thereof. Background Art

[0002] Friction materials are functional composite materials with friction and wear performance as their main working properties. As key functional materials, they play a vital role in the fields of industry and transportation. From the earliest asbestos-based materials to modern high-performance composite materials, the development of friction materials has undergone a technological revolution. With the diversification of application scenarios and the improvement of performance requirements, traditional friction materials can no longer meet the increasingly stringent working conditions, which has led to the development of new friction materials. Carbon-based ceramic friction materials, usually referring to carbon fiber reinforced silicon carbide ceramic-based composite materials, have been widely used in modern industry due to their excellent high temperature resistance, excellent wear resistance and stable friction coefficient. Carbon-based ceramic friction materials can maintain their performance under extreme conditions such as high temperature, high speed and heavy load, so they have important applications in automotive braking systems, thermal protection systems of aerospace vehicles, and transmission systems of high-end equipment. However, carbon-based ceramic friction materials themselves have some inherent limitations, mainly reflected in the greater brittleness of the material and relatively weak impact resistance, which limits their application in certain occasions that need to withstand large impact loads. In addition, due to the low thermal expansion coefficient of carbon materials, when connected to metal parts with higher thermal expansion coefficients, thermal stress is easily generated, which in turn causes cracks or delamination of the material, ultimately leading to early failure of the material.

[0003] As a high-performance engineering plastic, polyetheretherketone (PEEK) is widely recognized for its excellent mechanical properties, chemical resistance and wear resistance. The high temperature resistance of PEEK makes it have great application potential in friction materials, especially in automotive braking systems and transmission systems of high-end equipment. By introducing PEEK into friction materials, the toughness and impact resistance of the material can be significantly improved, thus overcoming the brittleness of traditional ceramic materials to a certain extent. PEEK material itself has good self-lubricating properties, which makes it an ideal friction-reducing and wear-resistant material and is widely used in various rotating and transmission devices. However, directly adding pure PEEK to carbon-based ceramic friction materials may also bring a series of challenges. First, the poor interface bonding between PEEK and inorganic fillers may form a weak link in the composite material, resulting in delamination or peeling under stress, which ultimately affects the overall performance of the material. In addition, with the increasing requirements for the application environment and service life of equipment, pure PEEK is difficult to meet more complex and demanding working conditions due to its low thermal stability and poor mechanical properties at high temperatures. For example, the increased brittleness of PEEK at high temperatures, the decreased shear performance, and the limited operating temperature all limit its application in certain high-performance fields. In view of the above, it is particularly important to modify PEEK to develop additives suitable for carbon-based ceramic friction materials. Through a reasonable modification process, the mechanical properties of PEEK can be improved, its wear resistance can be enhanced, and the modified PEEK can still maintain excellent friction properties under more demanding working conditions. Therefore, finding an effective modification method to prepare additives suitable for use in carbon-based ceramic friction materials is the key to the present invention. Summary of the invention

[0004] In order to solve the above problems, the present invention provides an additive for mixing with raw materials of a carbon-based ceramic friction material and a preparation method thereof.

[0005] In the first aspect, the present invention provides a method for preparing an additive for mixing a carbon-based ceramic friction material raw material, using the following technical scheme: A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 80-90°C, continue stirring for 3-6 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes and ultrasonically disperse to obtain a dispersion, and calcine the dispersion under the protection of inert gas to obtain multi-walled carbon nanotubes loaded with boron nitride; disperse the multi-walled carbon nanotubes loaded with boron nitride in THF, add a crosslinking agent and ultrasonically treat for 2-4 hours, centrifuge, wash, and dry to obtain a functional filler; S2: Add N-methylpyrrolidone and polyetheretherketone powder into a reaction kettle, heat to 130-160° C. and stir for 2-4 hours to dissolve the polyetheretherketone; then reduce the pressure to atmospheric pressure, add ethylenediamine, 3,3-diphenylpropylamine and palladium acetate, and continue to stir at 130-160° C. for 5-8 hours to perform chemical modification; after the reaction is completed, purify the modified polyetheretherketone by reduced pressure distillation; S3, mixing modified polyetheretherketone, functional filler, antioxidant, lubricant and dichloromethane, stirring and dissolving, concentrating and drying to remove the solvent, and obtaining a solid carbon-based ceramic friction material additive.

[0006] Preferably, the inert gas in step S1 is at least one of nitrogen, argon and helium.

[0007] Preferably, in step S1, the calcination temperature is 850-1050° C., and the calcination time is 4-6 hours.

[0008] Preferably, in step S1, the cross-linking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 1-3:1.

[0009] Preferably, in step S2, the components by weight include 100-120 parts of N-methylpyrrolidone, 16-20 parts of polyetheretherketone, 4-6 parts of ethylenediamine, 4-6 parts of 3,3-diphenylpropylamine and 0.05-0.08 parts of palladium acetate.

[0010] Preferably, in step S3, the components by weight include 46-50 parts of modified polyetheretherketone, 18-22 parts of functional filler, 1-3 parts of antioxidant, 4-6 parts of lubricant and 95-110 parts of dichloromethane.

[0011] Preferably, the antioxidant in step S3 is prepared by the following method: (1) Add butylated hydroxyanisole and butylated hydroxytoluene to ethanol and stir for 5-10 minutes until they are completely dissolved to obtain a mixed solution; (2) Add citric acid dropwise to the mixed solution, stir continuously for 20-35 min at 40-50°C until dissolved, adjust the pH to 6.0-7.0 after stirring evenly, let stand for 2-4 h, filter and dry to obtain the antioxidant.

[0012] Preferably, the lubricant in step S3 is at least one of zinc stearate, stearic acid and ethylene bisstearamide.

[0013] In a second aspect, the present invention also provides an additive for mixing raw materials of carbon-based ceramic friction materials, which adopts the following technical solution: An additive for mixing raw materials of carbon-based ceramic friction materials is prepared by the above preparation method.

[0014] In summary, the present invention has the following beneficial effects: The present invention proposes a method for preparing a carbon-based ceramic friction material additive, in which multi-walled carbon nanotubes loaded with boron nitride are used as functional fillers and are compounded with modified polyetheretherketone, antioxidants and other additives. Due to their thermal stability and toughness, multi-walled carbon nanotubes loaded with boron nitride can significantly enhance the mechanical properties of composite materials, improve the bearing capacity and impact resistance of friction materials, maintain the stability of materials under high temperature environments, and reduce material failure caused by overheating. By amino-modifying polyetheretherketone, the compatibility between polyetheretherketone and other components is improved, so that the components can be evenly dispersed to form a dense composite material structure, which helps to form a more uniform composite material, thereby improving the overall performance of the material. The presence of the antioxidant effectively prevents the oxidative aging of the material during high temperature and long-term use, prolongs the service life of the material, and ensures the long-term stability of the friction material. The additives prepared from functional fillers, modified polyetheretherketone, antioxidants and additives improve the friction coefficient, reduce wear, make the friction material more stable during operation, and reduce energy consumption. They not only improve the wear resistance and oxidation resistance of the friction material, so that it can still maintain a long service life under harsh conditions, but also improve its processing performance, making the friction material easier to form and process. By using ethylenediamine, 3,3-diphenylpropylamine and palladium acetate to modify polyetheretherketone, the surface active functional groups of PEEK after amination are increased, which can better interact with the inorganic components in the carbon-based ceramic material, help avoid local stress concentration caused by filler agglomeration, and thus improve the uniformity and reliability of the material. Due to its improved interface compatibility and dispersibility, it can simplify the processing technology of the composite material and reduce problems that occur during the processing, such as filler sedimentation and uneven distribution, thereby improving the quality of the finished product and production efficiency. Through chemical modification, the hardness and wear resistance of polyetheretherketone are enhanced, the wear of the friction material during use is reduced, and it has better anti-fatigue performance. It can maintain its structural integrity during repeated friction. By improving thermal stability, it can still maintain its original mechanical properties under high temperature conditions, reducing the degradation of material performance caused by temperature increase. In addition, the introduction of modified polyetheretherketone can make the friction coefficient of the friction material more controllable, which helps to maintain stable friction performance under different working conditions. The functional filler of the present invention is prepared by acid-treating multi-walled carbon nanotubes, loading boron nitride, and compounding with crosslinking agents (aminopropyltriethoxysilane and polyvinylpyrrolidone). The boron nitride coating formed at high temperature by the decomposition of sodium borate at high temperature and the action of ethylenediamine is directly grown on the carbon nanotubes through chemical reaction, so it has better chemical stability and is not easy to fall off or be damaged during processing. At the same time, by controlling the ratio of sodium borate and ethylenediamine and the calcination conditions, the state of the boron nitride coating can be more accurately controlled.The cross-linking agent prepared by mixing aminopropyl triethoxysilane and polyvinyl pyrrolidone can not only improve the compatibility of filler and matrix, but also further improve the uniform dispersion of filler in matrix through the synergistic effect of the two, avoid the aggregation of filler, and thus optimize the microstructure of composite material. Multi-walled carbon nanotubes loaded with boron nitride can effectively improve the thermal conductivity of materials, help heat dissipation, prevent material failure caused by local overheating, improve the strength and toughness of materials, and enable composite materials to maintain good performance when subjected to high stress. The antioxidant of the present invention is prepared by mixing butylated hydroxyanisole, butylated hydroxytoluene and citric acid. The synergistic effect between butylated hydroxyanisole and butylated hydroxytoluene can enhance their respective antioxidant properties, and the presence of citric acid can not only chelate metal ions, but also promote the dispersion of butylated hydroxyanisole and butylated hydroxytoluene in materials, further improving their antioxidant efficiency. By inhibiting oxidation reaction, antioxidant can effectively extend the service life of materials, and can also improve the thermal stability of materials during processing, and prevent premature aging or discoloration of materials under high temperature processing conditions, thereby improving product quality and production efficiency. DETAILED DESCRIPTION The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0015] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used are purchased from conventional biochemical reagent stores unless otherwise specified. The quantitative tests in the following examples were repeated three times, and the data are the average or average ± standard deviation of the three repeated experiments.

[0016] Preparation Example 1 The antioxidant is prepared by the following method: (1) adding butylated hydroxyanisole and butylated hydroxytoluene to ethanol, controlling the stirring speed to 400 r / min, stirring for 5 min until completely dissolved to obtain a mixed solution, wherein the mass ratio of ethanol, butylated hydroxyanisole and butylated hydroxytoluene is 30:1:1; (2) Add citric acid dropwise to the mixed solution, stir continuously for 35 min at 40 °C until dissolved, adjust the pH to 6.0 after stirring evenly, let stand for 2 h, filter and dry to obtain an antioxidant, wherein the mass ratio of the mixed solution to citric acid is 10:0.3.

[0017] Preparation Example 2 The antioxidant is prepared by the following method: (1) adding butylated hydroxyanisole and butylated hydroxytoluene to ethanol, controlling the stirring speed to 350 r / min, stirring for 8 min until completely dissolved to obtain a mixed solution, wherein the mass ratio of ethanol, butylated hydroxyanisole and butylated hydroxytoluene is 32:2:1; (2) Add citric acid dropwise to the mixed solution, stir continuously for 28 min at 45 °C until dissolved, adjust the pH to 6.5 after stirring evenly, let stand for 3 h, filter and dry to obtain an antioxidant, wherein the mass ratio of the mixed solution to citric acid is 12:0.4.

[0018] Preparation Example 3 The antioxidant is prepared by the following method: (1) adding butylated hydroxyanisole and butylated hydroxytoluene to ethanol, controlling the stirring speed to 300 r / min, stirring for 10 min until completely dissolved to obtain a mixed solution, wherein the mass ratio of ethanol, butylated hydroxyanisole and butylated hydroxytoluene is 35:3:3; (2) Add citric acid dropwise to the mixed solution, stir continuously for 20 min at 50 °C until dissolved, adjust the pH to 7.0 after stirring evenly, let stand for 4 h, filter and dry to obtain an antioxidant, wherein the mass ratio of the mixed solution to citric acid is 12:0.5.

[0019] Comparative Preparation Example 1 The antioxidant is prepared by the following method: (1) Add butylated hydroxyanisole to ethanol, control the stirring speed to 350 r / min, and stir for 8 minutes until it is completely dissolved to obtain a mixed solution, wherein the mass ratio of ethanol to butylated hydroxyanisole is 32:3; (2) Add citric acid dropwise to the mixed solution, stir continuously for 28 min at 45 °C until dissolved, adjust the pH to 6.5 after stirring evenly, let stand for 3 h, filter and dry to obtain an antioxidant, wherein the mass ratio of the mixed solution to citric acid is 12:0.4.

[0020] Comparative Preparation Example 2 The antioxidant is prepared by the following method: (1) Add butylated hydroxytoluene to ethanol, control the stirring speed to 350 r / min, and stir for 8 minutes until it is completely dissolved to obtain a mixed solution, wherein the mass ratio of ethanol to butylated hydroxytoluene is 32:3; (2) Add citric acid dropwise to the mixed solution, stir continuously for 28 min at 45 °C until dissolved, adjust the pH to 6.5 after stirring evenly, let stand for 3 h, filter and dry to obtain an antioxidant, wherein the mass ratio of the mixed solution to citric acid is 12:0.4.

[0021] Example 1 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 80°C, continue stirring for 6 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 1g:5ml:10ml; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes, ultrasonically disperse at 30kHz for 20min to obtain a dispersion, and calcine the dispersion at 850°C for 6h under nitrogen protection. A multi-walled carbon nanotube loaded with boron nitride is obtained, wherein the mass ratio of sodium borate, deionized water, ethylenediamine and pretreated multi-walled carbon nanotube is 2:12:1:1; the multi-walled carbon nanotube loaded with boron nitride is dispersed in THF, a cross-linking agent is added, ultrasonic treatment is performed at 30kHz for 2 hours, and then centrifugation, washing and drying are performed to obtain a functional filler, wherein the mass ratio of the multi-walled carbon nanotube loaded with boron nitride, THF and the cross-linking agent is 25:90:2, and the cross-linking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 1:1; S2. In parts by weight, 100 parts of N-methylpyrrolidone and 16 parts of polyetheretherketone polyetheretherketone powder are added to a reaction kettle, heated to 130° C. and stirred for 4 hours to dissolve the polyetheretherketone; then the pressure is reduced to atmospheric pressure, and 4 parts of ethylenediamine, 4 parts of 3,3-diphenylpropylamine and 0.05 parts of palladium acetate are added, and stirring is continued at 130° C. for 8 hours to carry out chemical modification; after the reaction is completed, the modified polyetheretherketone is purified by reduced pressure distillation; S3. Mix 46 parts of modified polyetheretherketone, 18 parts of functional filler, 1 part of antioxidant prepared in Preparation Example 1, 4 parts of zinc stearate and 95 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing carbon-based ceramic friction material raw materials.

[0022] Example 2 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 84°C, continue stirring for 5 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 2g:6ml:12ml; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes, ultrasonically disperse at 35kHz for 18min to obtain a dispersion, and calcine the dispersion at 900°C for 5h under nitrogen protection to obtain to multi-walled carbon nanotubes loaded with boron nitride, wherein the mass ratio of sodium borate, deionized water, ethylenediamine and pretreated multi-walled carbon nanotubes is 3:13:2:2; dispersing the multi-walled carbon nanotubes loaded with boron nitride in THF, adding a crosslinking agent, ultrasonically treating at 35kHz for 3.5h, centrifuging, washing and drying to obtain a functional filler, wherein the mass ratio of the multi-walled carbon nanotubes loaded with boron nitride, THF and the crosslinking agent is 27:92:4, and the crosslinking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 2:1; S2. Add 120 parts of N-methylpyrrolidone and 18 parts of polyetheretherketone polyetheretherketone powder in a reaction kettle by weight, heat to 140° C. and stir for 3.5 hours to dissolve the polyetheretherketone; then reduce the pressure to atmospheric pressure, add 5 parts of ethylenediamine, 5 parts of 3,3-diphenylpropylamine and 0.06 parts of palladium acetate, and continue to stir at 140° C. for 7.5 hours to carry out chemical modification; after the reaction is completed, purify the modified polyetheretherketone by reduced pressure distillation; S3. Mix 48 parts of modified polyetheretherketone, 19 parts of functional filler, 2 parts of antioxidant prepared in Preparation Example 2, 5 parts of zinc stearate and 96 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing carbon-based ceramic friction material raw materials.

[0023] Example 3 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 88°C, continue stirring for 4 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 2g:7ml:14ml; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes, ultrasonically disperse at 38kHz for 17min to obtain a dispersion, and calcine at 1000°C for 4.5h under nitrogen protection to disperse The boron nitride-loaded multi-walled carbon nanotubes are prepared by dispersing the multi-walled carbon nanotubes in THF, adding a cross-linking agent, ultrasonically treating the multi-walled carbon nanotubes at 38 kHz for 2.5 hours, centrifuging, washing, and drying to obtain a functional filler, wherein the mass ratio of the multi-walled carbon nanotubes loaded with boron nitride, THF, and the cross-linking agent is 28:98:4, and the cross-linking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 2:1; S2. In parts by weight, 115 parts of N-methylpyrrolidone and 19 parts of polyetheretherketone polyetheretherketone powder are added to a reaction kettle, heated to 150° C. and stirred for 3 hours to dissolve the polyetheretherketone; then the pressure is reduced to atmospheric pressure, and 5 parts of ethylenediamine, 5 parts of 3,3-diphenylpropylamine and 0.07 parts of palladium acetate are added, and the pressure is continued to be stirred at 150° C. for 7 hours for chemical modification; after the reaction is completed, the modified polyetheretherketone is purified by reduced pressure distillation; S3. Mix 49 parts of modified polyetheretherketone, 21 parts of functional filler, 2 parts of antioxidant prepared in Preparation Example 2, 5 parts of zinc stearate and 101 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing carbon-based ceramic friction material raw materials.

[0024] Example 4 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 90°C, continue stirring for 3 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 3g:8ml:15ml; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes, ultrasonically disperse at 40kHz for 15min to obtain a dispersion, and calcine the dispersion at 1050°C for 4h under nitrogen protection. A multi-walled carbon nanotube loaded with boron nitride is obtained, wherein the mass ratio of sodium borate, deionized water, ethylenediamine and pretreated multi-walled carbon nanotube is 6:15:3:3; the multi-walled carbon nanotube loaded with boron nitride is dispersed in THF, a cross-linking agent is added, ultrasonic treatment is performed at 40kHz for 2 hours, centrifugation is performed, washing and drying are performed to obtain a functional filler, wherein the mass ratio of the multi-walled carbon nanotube loaded with boron nitride, THF and the cross-linking agent is 30:100:5, and the cross-linking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 3:1; S2, by weight, add 120 parts of N-methylpyrrolidone and 20 parts of polyetheretherketone polyetheretherketone powder into a reaction kettle, heat to 160°C and stir for 2 hours to dissolve the polyetheretherketone; then reduce the pressure to atmospheric pressure, add 6 parts of ethylenediamine, 6 parts of 3,3-diphenylpropylamine and 0.08 parts of palladium acetate, continue to stir at 160°C for 5 hours for chemical modification; after the reaction is completed, purify the modified polyetheretherketone by reduced pressure distillation; S3. Mix 50 parts of modified polyetheretherketone, 22 parts of functional filler, 3 parts of antioxidant prepared in Preparation Example 3, 6 parts of zinc stearate and 110 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing carbon-based ceramic friction material raw materials.

[0025] Comparative Example 1 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 90°C, continue stirring for 3 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 3g:8ml:15ml; ultrasonically disperse ethanol, hexagonal boron nitride and pretreated multi-walled carbon nanotubes at 40kHz for 15min to obtain a dispersion, and calcine the dispersion at 1050°C for 4h under nitrogen protection to obtain a loaded nitrided carbon nanotube. Boron-loaded multi-walled carbon nanotubes, wherein the mass ratio of ethanol, hexagonal boron nitride and pretreated multi-walled carbon nanotubes is 15:3:3; multi-walled carbon nanotubes loaded with hexagonal boron nitride are dispersed in THF, a crosslinking agent is added, ultrasonic treatment is performed at 40kHz for 2 hours, centrifugation is performed, washing and drying are performed to obtain a functional filler, wherein the mass ratio of multi-walled carbon nanotubes loaded with boron nitride, THF and the crosslinking agent is 30:100:5, and the crosslinking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 3:1; S2. In parts by weight, 120 parts of N-methylpyrrolidone and 20 parts of polyetheretherketone polyetheretherketone powder are added to a reaction kettle, heated to 160° C. and stirred for 2 hours to dissolve the polyetheretherketone; then the pressure is reduced to atmospheric pressure, and 6 parts of ethylenediamine, 6 parts of 3,3-diphenylpropylamine and 0.08 parts of palladium acetate are added, and the pressure is continued to be stirred at 160° C. for 5 hours for chemical modification; after the reaction is completed, the modified polyetheretherketone is purified by reduced pressure distillation; S3. Mix 50 parts of modified polyetheretherketone, 22 parts of functional filler, 3 parts of antioxidant prepared in Preparation Example 3, 6 parts of zinc stearate and 110 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing carbon-based ceramic friction material raw materials.

[0026] Comparative Example 2 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 90°C, continue stirring for 3 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 3g:8ml:15ml; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes, and ultrasonically disperse at 40kHz for 15min to obtain a dispersion, and under nitrogen protection, at 105 The dispersion was calcined at 0°C for 4 hours to obtain multi-walled carbon nanotubes loaded with boron nitride, wherein the mass ratio of sodium borate, deionized water, ethylenediamine and pretreated multi-walled carbon nanotubes was 6:15:3:3; the multi-walled carbon nanotubes loaded with boron nitride were dispersed in THF, aminopropyltriethoxysilane was added, and after ultrasonic treatment at 40kHz for 2 hours, the functional filler was obtained by centrifugation, washing and drying, wherein the mass ratio of multi-walled carbon nanotubes loaded with boron nitride, THF and aminopropyltriethoxysilane was 30:100:5; S2. In parts by weight, 120 parts of N-methylpyrrolidone and 20 parts of polyetheretherketone polyetheretherketone powder are added to a reaction kettle, heated to 160° C. and stirred for 2 hours to dissolve the polyetheretherketone; then the pressure is reduced to atmospheric pressure, and 6 parts of ethylenediamine, 6 parts of 3,3-diphenylpropylamine and 0.08 parts of palladium acetate are added, and the pressure is continued to be stirred at 160° C. for 5 hours for chemical modification; after the reaction is completed, the modified polyetheretherketone is purified by reduced pressure distillation; S3. Mix 50 parts of modified polyetheretherketone, 22 parts of functional filler, 3 parts of antioxidant prepared in Preparation Example 3, 6 parts of zinc stearate and 110 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing carbon-based ceramic friction material raw materials.

[0027] Comparative Example 3 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 90°C, continue stirring for 3 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 3g:8ml:15ml; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes, and ultrasonically disperse at 40kHz for 15min to obtain a dispersion, and under nitrogen protection, at 1 The dispersion was calcined at 050°C for 4 hours to obtain multi-walled carbon nanotubes loaded with boron nitride, wherein the mass ratio of sodium borate, deionized water, ethylenediamine and pretreated multi-walled carbon nanotubes was 6:15:3:3; the multi-walled carbon nanotubes loaded with boron nitride were dispersed in THF, polyvinyl pyrrolidone was added and ultrasonically treated at 40kHz for 2 hours, and then centrifuged, washed and dried to obtain a functional filler, wherein the mass ratio of multi-walled carbon nanotubes loaded with boron nitride, THF and polyvinyl pyrrolidone was 30:100:5; S2. In parts by weight, 120 parts of N-methylpyrrolidone and 20 parts of polyetheretherketone polyetheretherketone powder are added to a reaction kettle, heated to 160° C. and stirred for 2 hours to dissolve the polyetheretherketone; then the pressure is reduced to atmospheric pressure, and 6 parts of ethylenediamine, 6 parts of 3,3-diphenylpropylamine and 0.08 parts of palladium acetate are added, and the pressure is continued to be stirred at 160° C. for 5 hours for chemical modification; after the reaction is completed, the modified polyetheretherketone is purified by reduced pressure distillation; S3. Mix 50 parts of modified polyetheretherketone, 22 parts of functional filler, 3 parts of antioxidant prepared in Preparation Example 3, 6 parts of zinc stearate and 110 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing carbon-based ceramic friction material raw materials.

[0028] Comparative Example 4 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 90°C, continue stirring for 3 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 3g:8ml:15ml; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes, ultrasonically disperse at 40kHz for 15min to obtain a dispersion, and calcine the dispersion at 1050°C for 4h under nitrogen protection. A multi-walled carbon nanotube loaded with boron nitride is obtained, wherein the mass ratio of sodium borate, deionized water, ethylenediamine and pretreated multi-walled carbon nanotube is 6:15:3:3; the multi-walled carbon nanotube loaded with boron nitride is dispersed in THF, a cross-linking agent is added, ultrasonic treatment is performed at 40kHz for 2 hours, centrifugation is performed, washing and drying are performed to obtain a functional filler, wherein the mass ratio of the multi-walled carbon nanotube loaded with boron nitride, THF and the cross-linking agent is 30:100:5, and the cross-linking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 3:1; S2. Add 120 parts of N-methylpyrrolidone and 20 parts of polyetheretherketone polyetheretherketone powder in a reaction kettle by weight, heat to 160° C. and stir for 2 hours to dissolve the polyetheretherketone; then reduce the pressure to atmospheric pressure, add 12 parts of ethylenediamine and 0.08 parts of palladium acetate, and continue to stir at 160° C. for 5 hours to carry out chemical modification; after the reaction is completed, purify the modified polyetheretherketone by reduced pressure distillation; S3. Mix 50 parts of modified polyetheretherketone, 22 parts of functional filler, 3 parts of antioxidant prepared in Preparation Example 3, 6 parts of zinc stearate and 110 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing carbon-based ceramic friction material raw materials.

[0029] Comparative Example 5 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 90°C, continue stirring for 3 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 3g:8ml:15ml; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes, ultrasonically disperse at 40kHz for 15min to obtain a dispersion, and calcine the dispersion at 1050°C for 4h under nitrogen protection. A multi-walled carbon nanotube loaded with boron nitride is obtained, wherein the mass ratio of sodium borate, deionized water, ethylenediamine and pretreated multi-walled carbon nanotube is 6:15:3:3; the multi-walled carbon nanotube loaded with boron nitride is dispersed in THF, a cross-linking agent is added, ultrasonic treatment is performed at 40kHz for 2 hours, centrifugation is performed, washing and drying are performed to obtain a functional filler, wherein the mass ratio of the multi-walled carbon nanotube loaded with boron nitride, THF and the cross-linking agent is 30:100:5, and the cross-linking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 3:1; S2. Add 120 parts of N-methylpyrrolidone and 20 parts of polyetheretherketone polyetheretherketone powder in a reaction kettle by weight, heat to 160° C. and stir for 2 hours to dissolve the polyetheretherketone; then reduce the pressure to atmospheric pressure, add 12 parts of 3,3-diphenylpropylamine and 0.08 parts of palladium acetate, and continue to stir at 160° C. for 5 hours to carry out chemical modification; after the reaction is completed, purify the modified polyetheretherketone by reduced pressure distillation; S3. Mix 50 parts of modified polyetheretherketone, 22 parts of functional filler, 3 parts of antioxidant prepared in Preparation Example 3, 6 parts of zinc stearate and 110 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing carbon-based ceramic friction material raw materials.

[0030] Comparative Example 6 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 90°C, continue stirring for 3 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 3g:8ml:15ml; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes, ultrasonically disperse at 40kHz for 15min to obtain a dispersion, and calcine the dispersion at 1050°C for 4h under nitrogen protection. A multi-walled carbon nanotube loaded with boron nitride is obtained, wherein the mass ratio of sodium borate, deionized water, ethylenediamine and pretreated multi-walled carbon nanotube is 6:15:3:3; the multi-walled carbon nanotube loaded with boron nitride is dispersed in THF, a cross-linking agent is added, ultrasonic treatment is performed at 40kHz for 2 hours, centrifugation is performed, washing and drying are performed to obtain a functional filler, wherein the mass ratio of the multi-walled carbon nanotube loaded with boron nitride, THF and the cross-linking agent is 30:100:5, and the cross-linking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 3:1; S2. In parts by weight, 120 parts of N-methylpyrrolidone and 20 parts of polyetheretherketone polyetheretherketone powder are added to a reaction kettle, heated to 160° C. and stirred for 2 hours to dissolve the polyetheretherketone; then the pressure is reduced to atmospheric pressure, and 6 parts of ethylenediamine, 6 parts of 3,3-diphenylpropylamine and 0.08 parts of palladium acetate are added, and the pressure is continued to be stirred at 160° C. for 5 hours for chemical modification; after the reaction is completed, the modified polyetheretherketone is purified by reduced pressure distillation; S3. Mix 50 parts of modified polyetheretherketone, 22 parts of functional filler, 3 parts of antioxidant prepared in Comparative Preparation Example 1, 6 parts of zinc stearate and 110 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing carbon-based ceramic friction material raw materials.

[0031] Comparative Example 7 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 90°C, continue stirring for 3 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 3g:8ml:15ml; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes, ultrasonically disperse at 40kHz for 15min to obtain a dispersion, and calcine the dispersion at 1050°C for 4h under nitrogen protection. A multi-walled carbon nanotube loaded with boron nitride is obtained, wherein the mass ratio of sodium borate, deionized water, ethylenediamine and pretreated multi-walled carbon nanotube is 6:15:3:3; the multi-walled carbon nanotube loaded with boron nitride is dispersed in THF, a cross-linking agent is added, ultrasonic treatment is performed at 40kHz for 2 hours, centrifugation is performed, washing and drying are performed to obtain a functional filler, wherein the mass ratio of the multi-walled carbon nanotube loaded with boron nitride, THF and the cross-linking agent is 30:100:5, and the cross-linking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 3:1; S2. In parts by weight, 120 parts of N-methylpyrrolidone and 20 parts of polyetheretherketone polyetheretherketone powder are added to a reaction kettle, heated to 160° C. and stirred for 2 hours to dissolve the polyetheretherketone; then the pressure is reduced to atmospheric pressure, and 6 parts of ethylenediamine, 6 parts of 3,3-diphenylpropylamine and 0.08 parts of palladium acetate are added, and the pressure is continued to be stirred at 160° C. for 5 hours for chemical modification; after the reaction is completed, the modified polyetheretherketone is purified by reduced pressure distillation; S3. Mix 50 parts of modified polyetheretherketone, 22 parts of functional filler, 3 parts of antioxidant prepared in Comparative Preparation Example 2, 6 parts of zinc stearate and 110 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing carbon-based ceramic friction material raw materials.

[0032] Comparative Example 8 A method for preparing an additive for mixing a carbon-based ceramic friction material raw material comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 90°C, continue stirring for 3 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use, wherein the mass volume ratio of multi-walled carbon nanotubes, concentrated nitric acid and concentrated hydrochloric acid is 3g:8ml:15ml; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes, ultrasonically disperse at 40kHz for 15min to obtain a dispersion, and calcine the dispersion at 1050°C for 4h under nitrogen protection. A multi-walled carbon nanotube loaded with boron nitride is obtained, wherein the mass ratio of sodium borate, deionized water, ethylenediamine and pretreated multi-walled carbon nanotube is 6:15:3:3; the multi-walled carbon nanotube loaded with boron nitride is dispersed in THF, a cross-linking agent is added, ultrasonic treatment is performed at 40kHz for 2 hours, centrifugation is performed, washing and drying are performed to obtain a functional filler, wherein the mass ratio of the multi-walled carbon nanotube loaded with boron nitride, THF and the cross-linking agent is 30:100:5, and the cross-linking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 3:1; S2. In parts by weight, 120 parts of N-methylpyrrolidone and 20 parts of polyetheretherketone polyetheretherketone powder are added to a reaction kettle, heated to 160° C. and stirred for 2 hours to dissolve the polyetheretherketone; then the pressure is reduced to atmospheric pressure, and 6 parts of ethylenediamine, 6 parts of 3,3-diphenylpropylamine and 0.08 parts of palladium acetate are added, and the pressure is continued to be stirred at 160° C. for 5 hours for chemical modification; after the reaction is completed, the modified polyetheretherketone is purified by reduced pressure distillation; S3. Mix 50 parts of modified polyetheretherketone, 22 parts of functional filler, 3 parts of antioxidant, 6 parts of zinc stearate and 110 parts of dichloromethane by weight, stir and dissolve, concentrate and dry to remove the solvent, and obtain an additive for mixing raw materials of carbon-based ceramic friction materials; wherein the antioxidant includes equal masses of butylated hydroxyanisole and dibutylated hydroxytoluene.

[0033] Performance Testing The carbon-based ceramic friction material raw material mixing additives, carbon black and alumina ceramic powder prepared in the embodiment and the comparative example were accurately weighed in a mass ratio of 5:1:1, and the above raw materials were added to a mixer, and stirred at 500 rpm for 30 minutes to ensure that there was no obvious component separation; the mixed powder was pressed in a press at 180° C. and 40 MPa for 5 minutes to form; after demolding the formed semi-finished product, it was first kept at 155° C. for 2.5 hours, kept at 135° C. for 2 hours, and kept at 175° C. for 2.5 hours, and then grooved and ground to obtain the friction material.

[0034] The friction material prepared above was subjected to the following performance tests: Friction coefficient measurement: The friction coefficient of the friction material was measured in accordance with the "SAE J2522" standard, and the measurement results are shown in Table 1. Wear resistance measurement: The mass wear of the friction material was measured in accordance with the GB / T 40398.1-2021 standard, and the measurement results are shown in Table 1. Tensile strength measurement: The tensile strength of the friction material was measured in accordance with the GBT33501-2017 standard, and the measurement results are shown in Table 1. Impact strength test: The impact strength of the friction material was measured in accordance with the GB / T 33835-2017 standard, and the measurement results are shown in Table 1. Table 1:

[0035] From the results shown in Table 1 above, it can be seen that the comprehensive performance of the additives for mixing carbon-based ceramic friction material raw materials prepared in Examples 1-4 of the present invention is much better than that of Comparative Examples 1-8.

[0036] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing an additive for mixing raw materials of carbon-based ceramic friction materials, characterized in that: The method comprises the following preparation steps: S1. Add multi-walled carbon nanotubes to a mixed acid solution of concentrated hydrochloric acid and concentrated nitric acid, heat to 80-90°C, continue stirring for 3-6 hours, wash and dry, and obtain pretreated multi-walled carbon nanotubes for use; dissolve sodium borate in deionized water, add ethylenediamine and stir evenly, add pretreated multi-walled carbon nanotubes and ultrasonically disperse to obtain a dispersion, and calcine the dispersion under the protection of inert gas to obtain multi-walled carbon nanotubes loaded with boron nitride; disperse the multi-walled carbon nanotubes loaded with boron nitride in THF, add a crosslinking agent and ultrasonically treat for 2-4 hours, centrifuge, wash, and dry to obtain a functional filler; S2: Add N-methylpyrrolidone and polyetheretherketone powder into a reaction kettle, heat to 130-160° C. and stir for 2-4 hours to dissolve the polyetheretherketone; then reduce the pressure to atmospheric pressure, add ethylenediamine, 3,3-diphenylpropylamine and palladium acetate, and continue to stir at 130-160° C. for 5-8 hours to perform chemical modification; after the reaction is completed, purify the modified polyetheretherketone by reduced pressure distillation; S3, mixing modified polyetheretherketone, functional filler, antioxidant, lubricant and dichloromethane, stirring and dissolving, concentrating and drying to remove the solvent, and obtaining a solid carbon-based ceramic friction material additive.

2. The method for preparing an additive for mixing raw materials of carbon-based ceramic friction materials according to claim 1, characterized in that: In step S1, the inert gas is at least one of nitrogen, argon and helium.

3. The method for preparing an additive for mixing raw materials of carbon-based ceramic friction materials according to claim 1, characterized in that: In step S1, the calcination temperature is 850-1050° C., and the calcination time is 4-6 hours.

4. The method for preparing an additive for mixing raw materials of carbon-based ceramic friction materials according to claim 1, characterized in that: In the step S1, the crosslinking agent is composed of aminopropyltriethoxysilane and polyvinylpyrrolidone in a mass ratio of 1-3:

1.

5. The method for preparing an additive for mixing raw materials of carbon-based ceramic friction materials according to claim 1, characterized in that: In step S2, the components by weight include 100-120 parts of N-methylpyrrolidone, 16-20 parts of polyetheretherketone, 4-6 parts of ethylenediamine, 4-6 parts of 3,3-diphenylpropylamine and 0.05-0.08 parts of palladium acetate.

6. The method for preparing an additive for mixing raw materials of carbon-based ceramic friction materials according to claim 1, characterized in that: In step S3, the components by weight include 46-50 parts of modified polyetheretherketone, 18-22 parts of functional filler, 1-3 parts of antioxidant, 4-6 parts of lubricant and 95-110 parts of dichloromethane.

7. The method for preparing an additive for mixing raw materials of carbon-based ceramic friction materials according to claim 1, characterized in that: The antioxidant in step S3 is prepared by the following method: (1) Add butylated hydroxyanisole and butylated hydroxytoluene to ethanol and stir for 5-10 minutes until they are completely dissolved to obtain a mixed solution; (2) Add citric acid dropwise to the mixed solution, stir continuously for 20-35 min at 40-50°C until dissolved, adjust the pH to 6.0-7.0 after stirring evenly, let stand for 2-4 h, filter and dry to obtain the antioxidant.

8. The method for preparing an additive for mixing raw materials of carbon-based ceramic friction materials according to claim 1, characterized in that: In step S3, the lubricant is at least one of zinc stearate, stearic acid and ethylene bisstearamide.

9. An additive for mixing raw materials of carbon-based ceramic friction materials, characterized in that: The carbon-based ceramic friction material is prepared by the method for preparing the additive for mixing raw materials according to any one of claims 1 to 8.

Citation Information

Cited By

  • Temperature-change-resistant memory sponge and preparation method thereof

    CN120399436A

  • Preparation method of fire-resistant special crucible

    CN121318464A

  • Method for producing a refractory special crucible

    CN121318464B